RATE OF DECOMPOSITION OF RABBIT CARCASSES IN DIFFERENT SEASONS OF ANDAMAN AND NICOBAR ISLANDS, INDIA - Kumar, Yogesh; Chauhan, Monika; De, Arun Kumar (Journal of Forensic Medicine and Toxicology, 2025)
Time since death is an important part of investigation. The major factors for estimation of time since death are environmental condition, and role of insects and their activities. In forensic taphonomy, the basic requirement to fulfill the requirement of post mortem estimation, are the reference data of decomposition in different climatic conditions with some other factors in a particular area. In India, very few studies have been done region wise. But, in Andaman and Nicobar Islands, India, this is the first study considering forensic entomology and taphonomy. In the four experiments of this study done on the rabbit carcasses (Oryctolagus cuniculus), the basic idea of on rate of decomposition and forensically important insects has been collected. In this study, the duration of rate of decomposition in rainy season of A&N Islands is noticed faster than summer season. The role of temperature and ants are also found affecting rate of decomposition.
Keywords: forensic taphonomy; orensic entomology; time since death; post mortem interval; forensically important insects etc